Effect of clamshells filler loading on the tensile properties of polyhydroxybutyrate - Othman, Maizatulnisa; Hashim, Mohd Yusoff; Ibrahim, Nor Azowa; Khalid, Khalisanni; Mohamad, Souad A. (Trans Tech Publications, Switzerland, 2015)
In this study, the abundant availability of clamshell, as the potential of the biomass resources for the production of the inorganic filler such as calcium carbonate (CaCO3) and calcium oxide (CaO) is fully utilized. In addition, the effect of filler loadings toward mechanical properties of polyhydroxybutyrate (PHB) biopolymer was studied using various ranges of loadings such as 10, 20, 30, 40 and 50 wt%. The tensile strength and modulus of PHB showed significant improvement with the incorporation of the filler up to 30 wt %, and this finding was supported by micrographs obtained from scanning electron microscope (SEM) which revealed uniform distribution of the filler in the polyhydroxybutyrate region. However, the elongations at break of the specimen shows vice versa, they start to deteriorate with the addition of the filler.